2015
DOI: 10.1186/s12979-015-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

End stage renal disease patients have a skewed T cell receptor Vβ repertoire

Abstract: BackgroundEnd stage renal disease (ESRD) is associated with defective T-cell mediated immunity. A diverse T-cell receptor (TCR) Vβ repertoire is central to effective T-cell mediated immune responses to foreign antigens. In this study, the effect of ESRD on TCR Vβ repertoire was assessed.ResultsA higher proportion of ESRD patients (68.9 %) had a skewed TCR Vβ repertoire compared to age and cytomegalovirus (CMV) – IgG serostatus matched healthy individuals (31.4 %, P < 0.001). Age, CMV serostatus and ESRD were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…With different techniques, it was shown that the TCR repertoire of patients with ESRD was skewed because of oligoclonal expansion of specific T cell populations [67,68]. In addition, the PERK phosphorylation pathway in CD4 T cells was disturbed, analogous to what has been described in elderly healthy individuals [69].…”
Section: Renal Failure and Adaptive Immunitymentioning
confidence: 94%
“…With different techniques, it was shown that the TCR repertoire of patients with ESRD was skewed because of oligoclonal expansion of specific T cell populations [67,68]. In addition, the PERK phosphorylation pathway in CD4 T cells was disturbed, analogous to what has been described in elderly healthy individuals [69].…”
Section: Renal Failure and Adaptive Immunitymentioning
confidence: 94%
“…Huang et al assessed the factors that may accelerate the TCR β repertoire contraction. They showed that age, CMV infection, and ESKD were significantly and independently associated with a shrinking of the TCR β repertoire (41). The impact of age on the TCR β repertoire concerned only the CD8 + memory T-cell subset but not the naive T-cell subset.…”
Section: Immunological Aspect Of Aging In Kidney Transplant Recipientsmentioning
confidence: 99%
“…Blood was drawn from KT-recipients the day before KT. Isolated PBMCs were stored at -150˚C with a minimum amount of 10×10 6 cells per vial until further analysis.…”
Section: Pbmc Isolationmentioning
confidence: 99%
“…Progressive loss of renal function leading to end-stage renal disease (ESRD) is associated with premature ageing of the T-cell system. The pro-inflammatory environment resulting from loss of renal function results in a lower thymic output, increased T-cell differentiation, telomere shortening and skewing of the T cell receptor (TCR) repertoire [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%